Upaya Meningkatkan Kemampuan Motorik Kasar Anak Melalui Kegiatan Melompat Tali di TK Family - Darsih Darsih; Melvi Lesmana; Mohammad Fauziddin (Jurnal Pendidikan Tuntas, 2023)
This study aims to improve student’s gross motor skills through Group B Jumping Rope activities at Family Kindergarten in the 2022/2023 school year. This research is a type of Classroom Action Research with collaborative methods. The subjects of this study were students in Group B. The objects in this study were students aged 5-6 years with elements that support students' gross motor skills, especially strength and balance. The data collection technique is observation (checklist). The research instrument is an observation sheet. Data analysis techniques using descriptive qualitative and quantitative. This classroom action research was carried out in two cycles.The steps for jumping rope activities are with the children warming up first, after that the children are divided into two groups, the next step is for the children to jump rope at ankle height, knee and thigh. The child who has already jumped the rope is given a reward. The gross motor elements observed in rope jumping activities in Cycle I and Cycle II were strength and balance. The results of the study show that the ability to improve gross motor skills can be improved by using rope jumping activities. Improved gross motor skills can be seen at the time before the action obtained 0% or 0 children out of 14 children in good criteria, in Cycle I obtained 42.85% or 6 children out of 14 children in good criteria, and Cycle II obtained 85.71% or 12 children out of 14 children in good criteria. Children can make jumps with the strength and balance of their feet so that they land well.